LITERATURE OF REVIEW THE INFLUENCE OF COMMUNICATION AND WORK LOYALTY ON EMPLOYEE PERFORMANCE AT PT. ARNOTT’S INDONESIA - Dewi Puspaningtyas Faeni; Angga Ian Saputra (Draf Solusi Indonesia, 2024)
This study is a design literature review that looks at how loyalty and communication affect worker performance. At PT. Arnott’s Indonesia, this study was carried out. In order to solve research difficulties utilizing the questionnaire method, this study employs a quantitative methodology. In order to assess the data's viability and make inferences regarding the hypothesis, this study will employ SPSS as a statistical tool.